INOVASI ICE LIME TEA CHIA SEED SEBAGAI MINUMAN SEHAT DENGAN PEMANIS STEVIA - Mila Noviana; Baiq Maria Estiani (PT PUSTAKA CENDEKIA GROUP, 2026)
Modern lifestyle changes that tend to consume high-sugar, low-nutrient drinks contribute to an increased risk of health problems, particularly heart disease. This study aims to develop an innovative functional drink, Ice Lime Tea Chia Seed, sweetened with stevia as a healthy and nutritious alternative drink that supports heart health. This product combines tea, lime, chia seeds, and stevia, which are known to contain antioxidants, fiber, omega-3, and are low in calories and sugar. The research method was carried out through descriptive product formulation stages. The development results show that the Ice Lime Tea Chia Seed drink has a fresh taste, is low in sugar, and contains nutrients that have the potential to help maintain heart health, improve body hydration, and support a healthy lifestyle. The use of stevia as a natural sweetener also provides added value because it is safer for consumers who limit their sugar consumption. Thus, this beverage innovation is expected to be a functional beverage solution that is healthy, practical, and in accordance with the needs of society in the modern era.